SAR Studies on Carboxylic Acid Series M1 Selective Positive Allosteric Modulators (PAMs) - D. Kuduk, Scott; C. Beshore, Douglas (Current Topics in Medicinal Chemistry, 2014)
There is mounting evidence from preclinical and early proof-of-concept studies suggesting that selective modulation of the M1 muscarinic receptor is efficacious in cognitive models of Alzheimer's disease (AD). A number of nonselective M1 muscarinic agonists have previously shown positive effects on cognitive function in AD patients, but were limited due to cholinergic adverse events thought to be mediated by pan activation of the M2 to M5 sub-types. Thus, there is a need to identify selective activators of the M1 receptor to evaluate their potential in cognitive disorders. One strategy to confer selectivity for M1 is the identification of allosteric agonists or positive allosteric modulators, which would target an allosteric site on the M1 receptor rather than the highly conserved orthosteric acetylcholine binding site. BQCA has been identified as a highly selective carboxylic acid M1 PAM and this review focuses on an extensive lead optimization campaign undertaken on this compound.
Keywords: quinolone